Dispositivos electrónicos utilizados en generadores eléctricos - Pahuanquiza Guamantica, Javier Alberto (2015)
The objective of this research is to show everything about electronic devices found in an electric generator and its functions the types of faults in this way to verify the protections used for a generator there is some kind of failure, the criteria applicable acceptance and effectiveness to indicate the type of generator to be used instantly buying or design, so it is vital to know your state to implement corrective actions required. The electric motors and generators are a group of devices used to convert mechanical energy into electrical, or conversely, with electromagnetic means. A machine that converts mechanical energy into electricity is called a generator, alternator or dynamo, and a machine that converts electrical energy into mechanical is called motor.